A Comparative Analysis of Survival and Funding Discrepancies in Cancers With High Mortality. Issue 2 (February 2020) - Hall, Bradley R.; Cannon, Andrew; Atri, Pranita; Wichman, Christopher S.; Smith, Lynette M.; Kumar, Sushil; Batra, Surinder K.; Wang, Hongmei; Ganti, Apar Kishor; Sasson, Aaron R.; Are, Chandrakanth
Abstract : Objective: Comparative analyses of survival and funding statistics in cancers with high mortality were performed to quantify discrepancies and identify areas for intervention. Background: Discrepancies in research funding may contribute to stagnant survival rates in pancreatic ductal adenocarcinoma (PDAC). Methods: The Surveillance, Epidemiology, and End Results database was queried for survival statistics. Funding data were obtained from the National Cancer Institute (NCI). Clinical trial data were obtained from www.clinicaltrials.gov . Cancers with high mortality were included for analyses. Results: Since 1997, PDAC has received lesser funding ($1.41 billion) than other cancers such as breast ($10.52 billion), prostate ($4.93 billion), lung ($4.80 billion), and colorectal ($4.50 billion). Similarly, fewer clinical trials have been completed in PDAC (n = 608) compared with breast (n = 1904), lung (n = 1629), colorectal (n = 1080), and prostate (n = 1055) cancer. Despite this, since 1997, dollars invested in PDAC research produced a greater return on investment with regards to 5-year overall survival (5Y-OS) compared with breast, prostate, uterine, and ovarian cancer. Incremental cost-effectiveness analysis demonstrates that millions (liver, non-Hodgkin lymphoma, and melanoma) and billions (colorectal and lung) of dollars were required for each additional 1% increase in 5Y-OS compared with PDAC. Funding of research towards early diagnosis of PDAC has decreased by 19% since 2007. For nearly all cancers, treatment-related research receives the highest percentage of NCI funding. Conclusions: Funding of PDAC research is significantly less than other cancers, despite its higher mortality and greater potential to improve 5Y-OS. Increased awareness and lobbying are required to increase funding, promote research, and improve survival. Abstract : Supplemental Digital Content is available in the text